Songs and Rhymes - Published by Ladybird Books (London Ladybird Books, 2007)
Containing the words to all of the songs and rhymes from the hit TV show, this book takes us on a little journey around the garden to meet Igglepiggle, Upsy Daisy, Makka Pakka, and all of the other friends from the Night Garden. It is suitable for little Night Garden fans.
Keywords: Stories in rhyme. -- Board books -- Pictorial works